2010
DOI: 10.3892/ijo_00000710
|View full text |Cite
|
Sign up to set email alerts
|

Fructose as a carbon source induces an aggressive phenotype in MDA-MB-468 breast tumor cells

Abstract: Aberrant glycosylation is a universal feature of cancer cells, and certain glycan structures are well-known markers for tumor progression. Availability and composition of sugars in the microenvironment may affect cell glycosylation. Recent studies of human breast tumor cell lines indicate their ability to take up and utilize fructose. Here we tested the hypothesis that adding fructose to culture as a carbon source induces phenotypic changes in cultured human breast tumor cells that are associated with metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…3b). This is consistent with literature that described that fructose is associated with more aggressive/metastatic phenotype of breast cancer cells (24) and its transporters (GLUT2 and GLUT5) are linked to numerous diseases and syndromes including breast cancer (25). Strikingly, while sucrose diet continually increased the breast tumor 12-HETE production (289.3±65.6 ng/mg protein), average tumor 12-HETE concentration was significantly higher in tumors from mice fed with fructose (333.1±58.6 ng/mg protein) and with fructose plus glucose diets (521.3±57.3 ng/mg protein) compared to the 12-HETE levels in control diet fed mice (186.2±25.5 ng/mg protein) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…3b). This is consistent with literature that described that fructose is associated with more aggressive/metastatic phenotype of breast cancer cells (24) and its transporters (GLUT2 and GLUT5) are linked to numerous diseases and syndromes including breast cancer (25). Strikingly, while sucrose diet continually increased the breast tumor 12-HETE production (289.3±65.6 ng/mg protein), average tumor 12-HETE concentration was significantly higher in tumors from mice fed with fructose (333.1±58.6 ng/mg protein) and with fructose plus glucose diets (521.3±57.3 ng/mg protein) compared to the 12-HETE levels in control diet fed mice (186.2±25.5 ng/mg protein) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Fructose has previously been reported to alter the glycan structures on the cell surface of tumor cells and increase their proliferative and invasive properties when compared to glucose in vitro (Monzavi-Karbassi et al, 2010). Our data demonstrated that altered fructose utilization plays a key role in AML progression as evidenced by an exacerbated leukemic phenotype regardless of the concentration of glucose present.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, intake of sugar enhances cellular proliferation and migration, induces DNA damage, and increases inflammation (44). Furthermore, an in vitro study on breast tumor cells showed that, although fructose appears to increase cell invasion and migration, glucose seems to increase cell proliferation (45). Excessive sugar consumption is also associated with an increase in the production of insulin that could increase IGF-I (46), which is a growth factor that has mitogenic and antiapoptotic effects on cells (47).…”
Section: Discussionmentioning
confidence: 99%